Otimização logística de unidades armazenadoras de soja e milho no estado do Paraná - Souza, Adriana Ireno de (2019)
Given the importance of agribusiness for the Brazilian economy and the existing deficit between grain production and storage capacity in Brazil, this research aims to analyze the location structure of soybean and corn storage units in the state of Paraná, Brazil. from the perspective of logistics optimization. The instrument used was the exploratory data analysis, by sizing the production of soybean and corn, the static capacities of the storage centers of each municipality, the exported volume of soybean and corn produced in Paraná, the distances between production, storage and exportation, transportation and storage costs. Spatial autocorrelation and linear programming were also used to propose a model. The results obtained were: the state of Paraná is one of the main soybean and corn producers and has an increasing evolution; The state's static storage capacity, despite growing in absolute terms, does not keep up with the growth rate of soybean and corn production and decreases relative to the national static capacity, and presents a deficit between production and storage; The state contributes significantly to Brazil's total soybean and corn exports to our largest trading partner, China; The most relevant item in the composition of logistics costs is distance.